Intrathecal administration of SRT1720 relieves bone cancer pain by inhibiting the CREB/CRTC1 signalling pathway. (10th January 2020) - Yang, Chengwei; Huang, Xiang; Wang, Sheng; Han, Mingming; Kang, Fang; Zhang, Zhi; Li, Juan
Highlights: SRT1720 treatment produced a dose-dependent analgesic effect on the BCP mice. The CREB/CRTC1 signalling pathway was upregulated in a mouse model of BCP. SRT1720 relieved BCP by inhibiting the CREB/CRTC1 signalling pathway. Abstract: Bone cancer pain (BCP) caused by primary or metastatic bone tumours significantly interferes with the quality of life of patients. However, the relief of BCP remains a major challenge. Our previous study demonstrated that intrathecal administration of the Sirtuin 1 (SIRT1) activator SRT1720 attenuated BCP in a murine model. Nevertheless, the underlying mechanisms have not been fully clarified. Previous studies demonstrated that the activation of the cAMP response element binding (CREB) protein played a critical role in BCP. Furthermore, SIRT1 can also regulate the balance between glucose and lipid metabolism through CREB deacetylation. In this study, we measured the analgesic effects of different intrathecal doses of SRT1720 on BCP in a murine model and further examined whether SRT1720 attenuated BCP by suppressing CREB/CREB-regulated transcription coactivator 1 (CRTC1) signalling pathway. Our results demonstrated that the BCP mice developed significant mechanical allodynia and spontaneous flinching, which were accompanied by the upregulation of phospho-Ser133 CREB (p-CREB) and CRTC1 expression in the spinal cord. SRT1720 treatment produced a dose-dependent analgesic effect on the BCP mice and downregulated the expression of p-CREB and CRTC1. These results suggest that intrathecal administration of SRT1720 reverses BCP likely by inhibiting the CREB/CRTC1 signalling pathway.